ChemInform Abstract: The Winding Pathway to Erythropoietin Along the Chemistry—Biology Frontier: A Success at Last. Issue 40 (12th September 2013) - Wilson, Rebecca M.; Dong, Suwei; Wang, Ping; Danishefsky, Samuel J.
Abstract Review: <70 refs.